Identificazione di specie dello stoccafisso, nell'ottica dell'ispezione sanitaria di prodotto - Bertoja, Gianluca (Università degli studi di Padova, 2008)
According to regulations in force in the hygiene sector (EC norms 178/2002, 852-853-854/2004, 2073/2005, 333/2007 and 1441/2007 ), this study involved the preparation of a traceability/retraceability model covering the many, varied, hygienic and health problems concerning stockfish, a traditionally important and significant product from the Italian fishing industry. This research was rendered more salient partly as a result of the modification of August 5 2005 to Italian Ministerial Decree of January 14 2005, regarding the Italian name for fish species of commercial interest. To receive the official denomination of stockfish species, two Gadids were identified: Gadus morhua (Gm) and Gadus macrocephalus. Study of the philogenesis and morphology of the Gadidae - with philogenetics, physiology, reproduction, type of fishing practised, on-board processing of catch (severing of jugular vein, decapitation, evisceration, removal of tail bone, descaling, washing, refrigeration), natural drying, and final classification of the product according to quality and size criteria -involves examination of how a single stage or a few stages may have a considerable effect, positive or negative, on the quality of the fresh or finished product. These aspects were discussed during two workshops at Tromsø and Høvik, in Norway. Comparisons revealed clearcut experimental guidelines for the primary filière of stockfish, highlighting risk assessment and identifying "Critical Points". Study continued in the field of molecular biology, for definitive identification of the species, both fresh and dried, in a rapid, precise and economical manner. For this purpose, muscle portions from 10 specimens of Gm were sampled, belonging to various populations found off the Norwegian coasts and others belonging to species philogenetically close to Gm, from a similar geographical habitat: Micromesistius poutassou, Melanogrammus aeglefinus, Gadiculus argenteus, Gadus (Merlangius) merlangus, Brosme brosme and Pollachius virens. These species, as regards ...